Pandangan Bangsawan Sasak Terhadap Perkawinan Bangsawan Dengan Non Bangsawan Antar Suku (Studi Kasus di Desa Penujak Kecamataan Praya Barat Kab.Lombok Tengah) - Evanurfitriani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Marriage is an innate bond between a man and a woman as a wife with the aim of forming a happy and eternal family (household) based on the One Godhead, Meanwhile in a traditional marriage a noble woman is strictly forbidden to marry a man who is not a noble, because her royal status is considered to be lost. Framework of thought and insight in community life, there is a custom that applies to a society that is very thick and upheld, such as the customs in Penujak Village, Praya District, Central Lombok Regency in the form of marriage. In marriage affairs, they must find a man who is able and can pay a high price and marriage with a non-noble man is a very genius violation of custom. Not only that, marriage between groups or with someone from outside who is categorized as violating customary law. Meanwhile, the custom that prevails in Penujak Village determines that a woman can only marry a man who only comes from the descendants of the nobility. However, the life of the Sasak tribe community in Penujak Village, aristocratic marriage, for example, with men from the lower social status layer (Non-Noble), the daughter of the noble descendant will be exiled (banished) and can even cause a commotion between the noble family and the non-noble family of the Sasak tribe. Meanwhile, Sasak women who carry out inter-tribal marriages with non-noble Javanese tribes do not receive any customary law sanctions. Even though customary norms are still very thick applicable to Sasak women who marry non-nobles of the Sasak tribe. Why is the marriage between the Sasak tribe which is different from the ordinary Sasak tribe, not accepted and sanctioned such as being exiled and not recognized by the extended family., but when the marriage between the Sasak tribe nobles and non-nobles from other tribes is accepted and does not receive resistance.it is appropriate for the Sasak tribe nobles and non-Sasak tribe nobles even the sonnatu of the Javanese tribe (outside Sasak) is not a noble, it is privileged and given a place of residence such as the mennatu who are of noble descent.